Public participation in planning a comfortable urban environment on the example of the Arkhangelsk region - Alexei G. Demenev; Tatiana F. Shubina; Polina V. Shubina; Marina V. Nenasheva; Artem V. Makulin; Ivan A. Tarasov (Arctic and North, 2018)
The article analyzes the experience of public participation in the planning of a comfortable urban environment. The forms of public involvement in the formation of a comfortable urban environment and their implementation are considered on the example of the Arkhangelsk region. The method of complex analysis of the theory and practice of public communications helps the article to present a qualitative as-sessment of public involvement in the improvement of the urban environment. It is shown that the existing methods of interaction between the authorities and citizens represent a one-sided process and often they are reduced to the formal fulfillment of legal requirements by municipalities. To improve the efficiency of public participation, the authors propose to develop a communicative model of urban space management based on constant interaction between municipal authorities and citizens. This model will allow establishing a dialogue between all stakeholders, which will ultimately lead to the successful implementation of the urban environmental program and improve the quality of life of citizens.